2004
DOI: 10.1186/1479-5868-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Activities Contributing to Total Energy Expenditure in the United States: Results from the NHAPS Study

Abstract: Background: Physical activity is increasingly recognized as an important factor influencing health and disease status. Total energy expenditure, both low-intensity and high-intensity, contributes to maintenance of healthy body weight. This paper presents the results of a quantitative approach to determining the activities that contribute to total energy expenditure in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 17 publications
(21 reference statements)
4
33
0
Order By: Relevance
“…However, the contribution of non-occupational non-leisure PA to total reported PA appeared modest, especially in men. It has been previously reported that household PA contributes more to total energy expenditure in women than in men [11]. Non-occupational non-leisure PA did not correlate significantly with the objective measure of total PA.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the contribution of non-occupational non-leisure PA to total reported PA appeared modest, especially in men. It has been previously reported that household PA contributes more to total energy expenditure in women than in men [11]. Non-occupational non-leisure PA did not correlate significantly with the objective measure of total PA.…”
Section: Discussionmentioning
confidence: 84%
“…As indicated in a recent update [3], activity can be accumulated ''from bouts lasting 10 or more min'', which should facilitate incorporation of PA in daily life. There is currently increasing interest in PA performed outside leisure and work [10][11][12][13][14][15][16][17]. Previous reports have shown that domestic PA can significantly contribute to the daily PA amount required to confer health benefits [6,10,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Included physical activities are derived from the most relevant daily-life and leisure time activities determined by the National Human Activities Patterns Survey. 42 The Block EES for physical activities uses six categories (rarely or never, a few times a month, 1-2 times/week, 3-4 times/week, 5-6 times/week and everyday) to assess frequency and seven categories (> 30 min, 30-59 min, 1 h, 1.5 h, 2 h, 3-4 h and > 4 h) to assess duration. The validation study showed that the percent of body fat predicted by levels of physical activity estimated from this questionnaire correlated well with the percent body fat observed.…”
Section: Methodsmentioning
confidence: 99%
“…William Langston, 2006; Siderowf & Lang, 2012; Stessman, Hammerman-Rozenberg, Cohen, Ein-Mor, & Jacobs, 2009) Furthermore, few studies have accounted for both leisure and non-leisure physical activity which is essential since the latter may constitute the majority of daily physical activity for many very old adults. (Dong, Block, & Mandel, 2004; Lin et al, 2011; Robertson, 2013) Thus, in the absence of studies employing validated objective measures of total daily physical activity, the natural history of physical activity in older adults and its role as a modifiable risk factor will remain unclear. (Baker, Francis, Soares, Weightman, & Foster, 2011; Daviglus Ml & et al, 2011)…”
Section: Introductionmentioning
confidence: 99%